Sumbang Duo Baleh: Cultural Heritage as the Foundation of Character Development in the Digital Age - Elpalina, Srimutia; Darmansyah, Darmansyah; Fitrisia, Azmi; Efi, Agusti; Erianjoni, Erianjoni; Agustina, Agustina (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study aims to analyze the role of Sumbang Duo Baleh, a Minangkabau traditional ethical guideline, as a foundation for character education in the digital era. It also explores strategies for integrating these values into formal and informal education to address modern challenges in moral development. This research employs a qualitative approach with a literature review and field observations conducted in schools in West Sumatra. Data collection methods include document analysis, interviews with teachers and cultural figures, and direct observations in educational settings. The data are analyzed using a descriptive qualitative method to examine a the relevance of Sumbang Duo Baleh in shaping students’ character amidst digital transformation. The findings reveal that Sumbang Duo Baleh remains relevant in guiding students’ ethical behavior despite the growing influence of digital culture. Its values can be effectively integrated into character education through curriculum adaptation, teacher and parent involvement, and the utilization of digital platforms. However, challenges such as the declining understanding of traditional values among younger generations and the influence of global digital trends must be addressed. The study implies that strengthening digital literacy with a cultural perspective and fostering collaboration between schools, families, and communities can enhance the effectiveness of character education. This research contributes to developing a character education model based on local wisdom that aligns with modern educational needs.